Rezension von: Lang, Adolf; Geiges, Leif, Altmühlfranken - Göpfert, Eberhard (Württembergisch Franken, 1989)
Adolf Lang; Leif Geiges: Altmühlfranken. Ein Führer durch Kunst und Geschichte. Stuttgart: Theiss 1987. 215 S., zahlr. Abb., Ktn.